The Effects of Dietary Protein and Lysine Levels on Broiler Performance, Carcass Characteristics and N Excretion - Rezaei, M.; Moghaddam, H. Nassiri; Reza, J. Pour; Kermanshahi, H. (International Journal of Poultry Science, 2004)
In a 2x3 factorial arrangement, the effects of dietary protein and lysine levels on performance and carcass characteristics of Ross male broiler chickens from 1 to 3 weeks and 4 to 6 weeks of age were tested. Dietary treatments consisted of three levels of L-lysine.HCl in starter and grower period (0.0, 1.5 and 3.0 g/kg) and two levels of protein (208.4, 178.4 in starter and 181.2, 161.2 g/kg in grower period) with 12.12 MJ AME/kg diet. Reducing dietary protein decreased weight gain in starter, grower and total period up to 6.0, 4.6 and 5.6% respectively (P